JURIDICAL ANALYSIS OF ACQUISITION OF LAND RIGHTS AS OBJECTS OF AGRARIAN REFORM IN THE PERSPECTIVE OF SETTLEMENT OF LAND TENURE IN FOREST AREAS (Research Study at The Karimun Regency Land Office) - Syafrizal; Soerya Respationo; Erniyanti; Dahlan; Sayid Fadhil (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Protected Forest Areas are forests or large areas of land that contain a collection of types of flora and fauna that form naturally or not. Forest areas designated as protected forest areas have a role as providers of clean water reserves, flood prevention, erosion protection, city lungs, and many more. The problems in this research are: How is the Legal Regulation of the Policy on Acquisition of Land Rights Objects of Agrarian Reform in the Perspective of Settlement of Land Tenure in Forest Areas, How is the Implementation of the Policy of Acquisition of Land Rights Objects of Agrarian Reform in the Perspective of Settlement of Land Tenure in Forest Areas, and What are the Factors? Constraints/Obstacles and Solutions to Policy Acquisition of Land Rights Objects of Agrarian Reform in the Perspective of Settlement of Land Tenure in Forest Areas. This research aims to determine the Legal Regulations for Acquisition of Land Rights for Objects of Agrarian Reform in the Perspective of Settlement of Land Tenure in Forest Areas. To find out how the policy for acquiring land rights over objects of agrarian reform is implemented in the perspective of resolving land tenure in forest areas, to find out the obstacles/obstacles and solutions to the policy of acquiring land rights over objects of agrarian reform in the perspective of resolving land tenure in forest areas. This research uses a descriptive method using a normative approach (Legal research) to obtain primary data through field research (research). The results of the research show that the Policy for Acquisition of Land Rights for Agrarian Reform Objects in the Perspective of Settlement of Land Tenure in Forest Areas (Research Study at the Karimun Regency Land Office) has basically been implemented well although there are still many obstacles in the field, especially the lack of professional and dedicated human resources high For this reason, it is hoped that the work mechanism of the Environment and Forestry Service of Riau Islands Province will be optimized so that obstacles related to the control of land rights in forest areas can be resolved.